Muqimiy va Zavqiy gʻazallarida ayrim tushunarsiz soʻzlarning leksik va morfologik tahlil - Abdurahmonova Gulorom, Gʻafforova Gulbahor, Boyqulova Sevara (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, words with incomprehensible meaning found in several obscure ghazals of Muhammad Aminkhoja Muqimi and Ubaidulla Zavqi are analyzed lexically and morphologically.